Pengaruh Pemasaran Langsung terhadap Keputusan Pembelian Produk Ms glow di Kota Padang Panjang dengan Customer Perceived Value sebagai Variabel Mediasi - Nadiatul Fadhilah; Rino Rino (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the impact of direct marketing and customer perceived value on Ms glow product purchasing decisions in the city of Padang Panjang. Causative descriptive research is the method used by the researcher. The people of Padang Panjang are the subjects of this study. Non-probability sampling with purposive sampling technique was used in this study, and the number of samples was determined using the Cochran formula to be as many as 97. The type of data used in this study is primary data obtained by distributing questionnaires to residents of Padang Panjang based on predetermined criteria, namely. clients who have used Ms glow products. The data used in this study was analyzed using SEM-PLS (Structural Equation Modeling -Partial Least Squares). The findings show that 1) Direct Marketing has a significant effect on Purchase Decisions, and 2) Customer Perceived Value has a significant effect on Purchase Decisions. 3) Customer Perceived Value is significantly influenced by direct marketing. 4) Through Customer Perceived Value, direct marketing has a significant impact on purchasing decisions for Ms glow products in the city of Padang Panjang.